Effects of Salicornia-Based Skin Cream Application on Healthy Humans' Experimental Model of Pain and Itching - Rocco Giordano; Giulia Erica Aliotta; Anja Stokholm Johannesen; Dina Voetmann-Jensen; Frederikke Hillebrand Laustsen; Lasse Allermann Andersen; Aman Rezai; Malthe Fredsgaard; Silvia Lo Vecchio; Lars Arendt-Nielsen; Mette Hedegaard Thomsen; Allan Stensballe (MDPI AG, 2022)
Halophyte plants are salt-tolerant and are acclimated for growth in saline soils such as along coastal areas. Among the halophytes, the Salicornia species have been used as both folk medicine and functional food for many years due to their high levels of bioactive compounds with supposed anti-inflammatory and antioxidative effects. However, the properties of Salicornia bioactive extracts on pain and itching still remain unclear. In this study, 30 healthy volunteers were randomized to treatments with 10% Salicornia-based cream or placebo cream for 24 or 48 h. On day 0, and 24 or 48 h post cream application, cold/heat detection and pain thresholds, mechanical pain thresholds and sensitivity, trans-epidermal water loss, histamine- and cowhage-evoked itch, and micro-vascular reactivity (neurogenic inflammation) were assessed to evaluate the analgesic, anti-pruritogenic and vasomotor effects. Skin permeability was reduced in the Salicornia-treated area for 48 h compared with 24 h application (p-value < 0.05). After 48 h of application, a decrease in mechanical-evoked itching (hyperkinesis) compared with 24 h treatment (p-value < 0.05) and increased warm detection and heat pain thresholds (p-value < 0.05) was found. Histamine-induced neurogenic inflammation showed a significant reduction in the cream-treated areas after 48 h compared with 24 h (p-value < 0.05). The results of this study indicate the overall inhibitory effect of Salicornia on hyperkinesis (mechanically evoked itch), the analgesic effect on thermal sensation, and modulation of the skin barrier architecture. Further studies are needed for the assessment of the long-term effects.